2020
DOI: 10.3390/jcm9093037
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte Chemoattractant Protein-1 Is an Independent Predictor of Coronary Artery Ectasia in Patients with Acute Coronary Syndrome

Abstract: Our purpose was to assess a possible association of inflammatory, lipid and mineral metabolism biomarkers with coronary artery ectasia (CAE) and to determine a possible association of this with acute atherotrombotic events (AAT). We studied 270 patients who underwent coronary angiography during an acute coronary syndrome 6 months before. Plasma levels of several biomarkers were assessed, and patients were followed during a median of 5.35 (3.88–6.65) years. Two interventional cardiologists reviewed the coronary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The extreme proteolysis of extracellular matrix (ECM) weakens the vessel architecture, increase the wall stress, and reduce vessel tolerance to blood flow, thus predisposing to the progressive dilatation of the artery. Moreover, chronic inflammation further contributes to arterial wall damage and dilatation, as demonstrated by the correlation between high levels of inflammatory markers and the presence and the severity of CAE (36)(37)(38). However, while inflammation represents one of the major features of the pathophysiology and natural history of atherosclerosis, recent findings demonstrated an increased inflammatory status in patients with CAE compared to those with CAD alone, with significantly higher levels of circulating cytokines (39).…”
Section: Etiopathogenesis and Pathophysiologymentioning
confidence: 99%
“…The extreme proteolysis of extracellular matrix (ECM) weakens the vessel architecture, increase the wall stress, and reduce vessel tolerance to blood flow, thus predisposing to the progressive dilatation of the artery. Moreover, chronic inflammation further contributes to arterial wall damage and dilatation, as demonstrated by the correlation between high levels of inflammatory markers and the presence and the severity of CAE (36)(37)(38). However, while inflammation represents one of the major features of the pathophysiology and natural history of atherosclerosis, recent findings demonstrated an increased inflammatory status in patients with CAE compared to those with CAD alone, with significantly higher levels of circulating cytokines (39).…”
Section: Etiopathogenesis and Pathophysiologymentioning
confidence: 99%
“…Of the 11 studies included, only 1 ( 22 ) was a retrospective cohort study and the others were prospective cohort studies, with a publication period from 2014 to 2020. Four trials ( 20 , 22 , 27 , 28 ) reported RRs according to continuous concentrations of PCSK9, three studies ( 19 , 24 , 26 ) reported RRs according to categorical levels, and four studies ( 8 , 21 , 23 , 28 ) reported RRs according to both continuous and categorical levels. We included 8,471 patients, and the sample size of each study ranged from 249 to 2,030.…”
Section: Resultsmentioning
confidence: 99%
“…We included 8,471 patients, and the sample size of each study ranged from 249 to 2,030. The longest follow-up was 5.35 years ( 20 ), and the mean weighted follow-up was 1.42 years. The baseline serum PCSK9 concentrations ranged from 52.1 to 607 ng/ml (weighted mean, 283.8 ng/ml).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with acute coronary syndrome, higher plasma levels of galectin-3 levels were found to be associated with poor survival rate [38]. Furthermore, high FGF-23 plasma levels have been shown to predict mortality and cardiovascular events [39,40], hs troponin and in further biomarker analysis, Galectin-3 didn't have a prognostic relevance in TTC. Galectin-3 was neither predictive for cardiac decompensation (rs: −0.152; p: 0.293), for arrhythmias (rs: −0.002; p: 0.990) nor all-cause complications (rs: −0.177, p: 0.219).…”
Section: Discussionmentioning
confidence: 99%